2009
DOI: 10.1073/pnas.0909293106
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of radiation-induced cognitive impairment through cranial transplantation of human embryonic stem cells

Abstract: Cranial irradiation remains a frontline treatment for the control of tumor growth, and individuals surviving such treatments often manifest various degrees of cognitive dysfunction. Radiation-induced depletion of stem/precursor cell pools in the brain, particularly those residing in the neurogenic region of the hippocampus, is believed, in part, to be responsible for these often-unavoidable cognitive deficits. To explore the possibility of ameliorating radiation-induced cognitive impairment, athymic nude rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(159 citation statements)
references
References 56 publications
4
151
1
Order By: Relevance
“…Recently, transplanting human ESCs into the hippocampus of athymic nude rats has been shown to improve cognitive impairment caused by irradiation. The transplanted cells can migrate to the subgranular zone and exhibit signs of neuron morphology within the neurogenic niche with no observed overt adverse cognitive sequelae or intracranial teratogenesis [10]. In contrast, our study detected teratomas in about 30% of irradiated hosts and 7.5% of unirradiated hosts.…”
Section: Dear Editorcontrasting
confidence: 49%
“…Recently, transplanting human ESCs into the hippocampus of athymic nude rats has been shown to improve cognitive impairment caused by irradiation. The transplanted cells can migrate to the subgranular zone and exhibit signs of neuron morphology within the neurogenic niche with no observed overt adverse cognitive sequelae or intracranial teratogenesis [10]. In contrast, our study detected teratomas in about 30% of irradiated hosts and 7.5% of unirradiated hosts.…”
Section: Dear Editorcontrasting
confidence: 49%
“…Past data in the same mouse background (i.e., C57Bl6) has found irradiation to elicit cognitive decrements, albeit at longer postirradiation intervals (9,10), and data from us and others using different strains of rat have shown irradiation to elicit hippocampal deficits in learning and memory (8,40,41). Recent data from us has also shown that lowdose irradiation of the same transgenic mouse strain with charged particles elicits decrements in cognition using a novel object recognition test (42).…”
Section: Discussionmentioning
confidence: 75%
“…Radiation Exposure. Mice 2-mo of age were anesthetized and exposed to cranial γ-irradiation (1 or 10 Gy) using a 137 Cs irradiator at a dose rate of 2.07 Gy/min, as previously described (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the recognition and prevalence of these adverse side effects, relatively few, if any, long-term satisfactory solutions exist for this unmet medical need. Past work from our laboratory has optimized transplantation parameters and established many of the long-term benefits of human stem cell-based therapies for the treatment of radiationinduced cognitive dysfunction (3)(4)(5). Cranially grafted stem cells have been shown to impart persistent improvements in behavioral performance in irradiated rats over extended postirradiation intervals (1-8 mo) using short-and long-term cognitive testing paradigms (4,6,7).…”
mentioning
confidence: 99%